GAMBARAN KLINIS TRAUMA UROLOGI DI RSUD ARIFIN ACHMAD PEKANBARU PERIODE JANUARI 2009 – DESEMBER 2013 - A, Sri Meutia; ", Zuhirman; Amelia, Siti Mona (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Urological trauma can present in kidney, ureter, bladder, urethra, penile, testis and scrotum. Urological trauma not only caused decrease quality of life but also create complicaton if not dealt with appropriately and quickly. This research was purposed to know clinical representation of urological trauma in RSUD Arifin Achmad Pekanbaru since Januari 2009 – Desember 2013. This study was a descriptive retrospective study. Data has shown 23 medical records of urological trauma parients. Result from this study is total of urological trauma is 38 cases of all trauma cases (0,40%) in RSUD Arifin Achmad Pekanbaru sinse Januari 2009 – Desember 2013. Urologic organ often affected is kidney is 8 cases (32%). Urological trauma patients There are 19 cases (82,6%) were males and 4 cases (17,4%) were females. The most common age was 20-30 years old (30,5%). The most coomon etiology of urological trauma was blunt trauma is 16 cases (69,5%) whereas the most management of urological trauma is konservatif as 21 cases (605). The multiple trauma of this research are one cases for trauma of urology organ with urology organ and two cases for urology organ and non urology organ.Keyword : urological trauma, urethral trauma, renal trauma, blunt trauma